Shelf-life of reduced-fat white chocolate fillings using iota-carrageenan - Dias, João; Alvarenga, Nuno; Sousa, Isabel (Emirates Journal of Food and Agriculture, 2017)
The conservation of traditional chocolate fillings can present some hurdles due to the use of perishable raw matters, physical changes during processing and to the influence of external factors, which tends to shorten shelf-life of traditional filled pralinés to only 3-4 months. The aim of this study was to evaluate the influence of the concentration of iota-carrageenan on chemical, rheological, image analysis and microbial properties of reduced-fat white chocolate fillings during storage time. Two batches of reduced-fat filling were produced using white chocolate, commercial grade sugar, skimmed milk, inverted sugar and iota-carrageenan (at 0.5 % w/w and 1.0 % w/w concentration) and stored at 4 ºC during 12 months. A control batch with no hydrocolloid was also produced. The results presented a decrease in pH, aw and moisture during storage time. The rheological characterization concluded that all formulations presented a shearthinning behaviour and both flow index (n) and consistency (K) were correlated with iota-carrageenan concentration and with storage time. The concentration of iota-carrageenan did not influence the digital image analysis of chocolate fillings, but a shift was observed during storage time, especially at the end. The microbial analysis showed a positive correlation to storage time in the formulation using 1.0 % iota-carrageenan, nevertheless all results were quite acceptable and within the recommended safety values.